Incidence of COVID-19 Symptom Rebound After Treatment with Remdesivir - Kalpana Gupta; William J. O’Brien; Judith Strymish; Anna Chen; Katherine Linsenmeyer; Rebecca Madjarov; Michael E. Charness (Infectious Disease Reports)
Background/Objectives: Recent in vitro data suggest that remdesivir might be less likely than nirmatrelvir–ritonavir to be associated with COVID-19 rebound. We compared the incidence of symptom rebound in our remdesivir-treated cohort with rates reported in the literature for nirmatrelvir–ritonavir. Methods: We performed a retrospective cohort study of VA Boston Healthcare System patients who were nursing home residents or inpatients treated with remdesivir for mild to moderate COVID-19 that met clinical criteria for nirmatrelvir–ritonavir treatment between 05/2022 and 10/2024. Electronic health records were reviewed for evidence of symptom rebound in daily clinical evaluations and outside hospital care notes for 15–20 days after the diagnosis of COVID-19. Rates for nirmatrelvir–ritonavir were identified via a literature review. Results: Among 194 patients treated with remdesivir, 39 were excluded due to concurrent antiviral use, hypoxia, or ICU-level care. The average age of the remaining 155 patients was 75.1 ± 11.9 years; 147 patients (95%) were male. Evidence of symptom rebound was found in 1 of 155 (0.6%) remdesivir-treated patients, which is a rate lower than that reported in all 12 studies of nirmatrelvir–ritonavir symptom rebound during the Omicron era. Conclusions: Our finding of low rates of COVID-19 symptom rebound after treatment with remdesivir are consistent with the hypothesis that rebound may be less frequent after treatment with remdesivir than with nirmatrelvir–ritonavir.